Hes3 is expressed in the adult pancreatic islet and regulates gene expression, cell growth, and insulin release - Masjkur, Jimmy; Arps-Forker, Carina; Poser, Stephen W.; Nikolakopoulou, Polyxeni; Toutouna, Louiza; Chenna, Ramu; Chavakis, Triantafyllos; Chatzigeorgiou, Antonios; Chen, Lan-Sun; Dubrovska, Anna; Choudhary, Pratik; Uphues, Ingo; et al. (American Society for Biochemistry and Molecular Biology, 2014)
The transcription factor Hes3 is a component of a signaling pathway that supports the growth of neural stem cells with profound consequences in neurodegenerative disease models. Here we explored whether Hes3 also regulates pancreatic islet cells. We showed that Hes3 is expressed in human and rodent pancreatic islets. In mouse islets it co-localizes with alpha and beta cell markers. We employed the mouse insulinoma cell line MIN6 to perform in vitro characterization and functional studies in conditions known to modulate Hes3 based upon our previous work using neural stem cell cultures. In these conditions, cells showed elevated Hes3 expression and nuclear localization, grew efficiently, and showed higher evoked insulin release responses, compared with serum-containing conditions. They also exhibited higher expression of the transcription factor Pdx1 and insulin. Furthermore, they were responsive to pharmacological treatments with the GLP-1 analog Exendin-4, which increased nuclear Hes3 localization. We employed a transfection approach to address specific functions of Hes3. Hes3 RNA interference opposed cell growth and affected gene expression as revealed by DNA microarrays. Western blotting and PCR approaches specifically showed that Hes3 RNA interference opposes the expression of Pdx1 and insulin. Hes3 overexpression (using a Hes3-GFP fusion construct) confirmed a role of Hes3 in regulating Pdx1 expression. Hes3 RNA interference reduced evoked insulin release. Mice lacking Hes3 exhibited increased islet damage by streptozotocin. These data suggest roles of Hes3 in pancreatic islet function.